The Students’ Frequency of Wacthing YouTube with Learning Contents and Their Speaking Skill at 4th Semester of English Department of IAIN - Endang Haryanto (AL LUGHAH, 2021)
The aim of this study is to find out whether there is a correlation between students’ frequency of using YouTube content and speaking skill at 4th semester of English Department of IAIN Bengkulu. This study was conducted in correlational research which involved 21 students. A questionnaire was used to obtain students’ frequency of using YouTube content and test was employed to obtain students’ speaking skill. Both data were calculated using Pearson Product Moment Formula and SPSS Program. The result of this study showed that the coefficient correlation (rcount) was higher than the rtable (0,852 > 0,433). It can be said that there is a significant correlation between students’ frequency of using YouTube content and their speaking skill at 4th semester of English Department of IAIN Bengkulu. The interpretation of correlation coefficient 0,852 was high correlation. The hypothesis accepted in this research was alternative hypothesis (Ha), whereas the null hypothesis (Ho) was rejected. In brief, it could be drawn that students’ frequency of using YouTube was correlated with their speaking skill.